The Family: A Key Environment for Deaf Students' Learning in Virtual Continuing Education Processes - Prado Ortega, Mauricio Xavier (2025)
Given the need for free training opportunities for deaf individuals, with digital competency content delivered in an inclusive manner, virtual education emerges as a key alternative to meet this demand. This study focuses on the role and involvement of families as a crucial factor in the educational success of deaf students, providing support throughout their virtual continuous education process. The primary aim of this research is to develop effective strategies for engaging family members in the comprehensive support of deaf students in virtual environments, thereby enhancing their motivation, access to technology, and time management. The study has a descriptive scope and a mixed-methods approach, focusing on virtual training for 28 deaf students at the Technical University of Machala in Ecuador. It included phases of virtual instruction, alongside collaboration with sign language interpreters. Data collection was carried out through online surveys conducted in the second half of 2023, followed by statistical analysis and scale evaluations to generate tables. Findings indicate that family awareness of emotional support and motivation is critical to their children's learning. The study emphasizes the importance of an inclusive educational environment that respects deaf identity and provides ongoing technical support. The most significant contribution of the family in the virtual training of deaf individuals is emotional, communicative, and adaptive support. It is recommended to train family members in digital competencies beforehand, to facilitate their access to platforms adapted to the needs of deaf individuals, such as those with automatic subtitles or real-time interpreters.